Physical Organohydrogels With Extreme Strength and Temperature Tolerance - Zhang, Jing Wen; Dong, Dian Dian; Guan, Xiao Yu; Zhang, En Mian; Chen, Yong Mei; Yang, Kuan; Zhang, Yun Xia; Khan, Malik Muhammad Bilal; Arfat, Yasir; Aziz, Yasir (Frontiers in Chemistry, 2020)
Tough gel with extreme temperature tolerance is a class of soft materials having potential applications in the specific field required excellent integrated properties under subzero temperature. Herein, physical crosslinked Eueopian (Eu)-alginate/polyvinyl alcohol (PVA) organohydrogels that do not freeze at far below 0°C, while retention of high stress and stretchability is demonstrated. These organohydrogels are synthesized through displacement of water swollen in polymer networks of hydrogel to cryoprotectants (e.g., ethylene glycol, glycerol and d-sorbitol). The organohydrogels swollen water-cryoprotectant binary systems can be recovered to their original shapes when bent, folded and even twisted after being cooled up to a temperature as low as -20°C and -45°C, due to lower vapor pressure and ice-inhibition of cryoprotectant. After being treated under subzero temperature, the physical organohydrogels exhibit the maximum stress (5.62±0.41 MPa) and strain (7.63±0.02), which is about 10 and 2 times of their original hydrogels, due to the synergistic effect of multiple hydrogen bonds, coordination bonds and the dense polymer networks. Based on these features, such physically crosslinked organohydrogels with extreme toughness together with wide temperature tolerance is a promising soft material expanding the applications of gels in more specific and harsh conditions.